2011
DOI: 10.1007/s10561-011-9252-6
|View full text |Cite
|
Sign up to set email alerts
|

Infectious disease screening of blood specimens collected post-mortem provides comparable results to pre-mortem specimens

Abstract: Serology assays for standard screening are optimised for use with sera collected from living adults and children. Because of potential changes in the vascular compartments after death, methods used for screening sera from cadaveric organ donors need to be validated before testing these specimens. Serum was separated from blood collected from cadaveric donors within 24 h of death and biochemical parameters measured to detect dilution of protein and haemolysis. In order to demonstrate if any inhibitors that migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The latter would cause antigen–antibody binding and potentially cause false‐positive results; however, it would not affect the TPLA test, which is specific for treponemal antigens. Baleriola et al reported that no interference was detected in postmortem samples spiked with aliquots of T. pallidum ‐positive sera, with no significant differences between the results of premortem versus postmortem samples . Even if this previous study by Baleriola et al was restricted to samples collected within 24 h of postmortem, these results would support the reliability of the positive TPLA test results in our case.…”
Section: Discussionsupporting
confidence: 79%
“…The latter would cause antigen–antibody binding and potentially cause false‐positive results; however, it would not affect the TPLA test, which is specific for treponemal antigens. Baleriola et al reported that no interference was detected in postmortem samples spiked with aliquots of T. pallidum ‐positive sera, with no significant differences between the results of premortem versus postmortem samples . Even if this previous study by Baleriola et al was restricted to samples collected within 24 h of postmortem, these results would support the reliability of the positive TPLA test results in our case.…”
Section: Discussionsupporting
confidence: 79%
“…Nonrelated ante- and postmortem clinical samples from cornea donors were analyzed by Baleriola et al [25]. Since data on the antemortem status of the cornea donors were unknown, a rate of possible false-negative results could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Of the currently available assays, the FDA-approved Architect HIV Ag/Ab Combo (HIV Combo) assay (Abbott Diagnostics) has shown promise as a screening tool with a reported sensitivity of 100% and specificity of 95 to 99% when evaluated on p24 antigen and HIV antibody clinical standards as well as panels of fresh and frozen clinical specimens (2,25,30,33). The HIV Combo assay is a chemiluminescent magnetic microparticlebased immunoassay that uses recombinant antigens derived from the transmembrane proteins of HIV-1 groups M and O and HIV-2 for antibody detection and monoclonal anti-p24 for antigen detection (25).…”
mentioning
confidence: 99%